The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1292/jvms.16-0183
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of type 2 diabetes by helminth-induced Th2 immune response

Abstract: Helminth-induced type 2 cytokines increase the number of regulatory T cells and alternatively activated macrophages, resulting in modulation of the host–immune system. Studies on these parasite-induced immunoregulatory mechanisms might contribute to the development of new therapies for inflammatory diseases, including type 2 diabetes (T2D). Previous studies have suggested that progression of obesity-associated metabolic abnormalities is under pathophysiological control of CD4+ T cells. Glucose absorption throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…However, the exact mechanisms are not fully understood, this was explained by the anti-inflammatory effect of helminths since helminthiasis lower the circulatory pro-inflammatory cytokines and increase the anti-inflammatory cytokines [ 30 , 31 ]. Helminths also lead to depletion of body energy sources resulting in weight loss and improved metabolic outcomes [ 27 29 ] as well as manipulate the gut microbiome that plays an essential role in blood glucose homeostasis [ 30 , 32 ]. The current study findings showed that the proportion of parasitosis was much higher in diabetic individuals and the odds of testing positive for either urogenital schistosomiasis or intestinal parasitic diseases were more than two times higher in T2DM compared to control individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanisms are not fully understood, this was explained by the anti-inflammatory effect of helminths since helminthiasis lower the circulatory pro-inflammatory cytokines and increase the anti-inflammatory cytokines [ 30 , 31 ]. Helminths also lead to depletion of body energy sources resulting in weight loss and improved metabolic outcomes [ 27 29 ] as well as manipulate the gut microbiome that plays an essential role in blood glucose homeostasis [ 30 , 32 ]. The current study findings showed that the proportion of parasitosis was much higher in diabetic individuals and the odds of testing positive for either urogenital schistosomiasis or intestinal parasitic diseases were more than two times higher in T2DM compared to control individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of both suggest they influence each other. Previous studies showed that some helminths infection or its derived antigens reduce blood glucose and improve insulin sensitivity [27][28][29][30][31]. However, the exact mechanisms are not fully understood, this was explained by the anti-inflammatory effect of helminths since helminthiasis lower the circulatory proinflammatory cytokines and increase the antiinflammatory cytokines [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have reported an inverse relationship between the incidence of helminth infection and type 2 diabetes (Aravindhan et al, 2010;Chen et al, 2013;Hays et al, 2015), and also serum levels of the pro-inflammatory cytokines IL-6 and GM-CSF (Aravindhan et al, 2010); these studies controlled for age and BMI (and/or income). And again, experimental helminth infections protected mice from type 2 diabetes-associated states such as hyperglycemia and insulin resistance (Wu et al, 2011;Morimoto et al, 2016;Pace et al, 2018), while anthelmintic treatment elevated blood glucagon and insulin resistance, and several circulating pro-inflammatory cytokines (Tahapary et al, 2017;Rajamanickam et al, 2019Rajamanickam et al, , 2020. Regarding atherosclerosis, the burden of Opisthorchis felineus (cat liver fluke) in cadavers was found to be negatively correlated with the severity of aortic atherosclerosis (Magen et al, 2013).…”
Section: Helminth Therapy To Counter Inflammaging?mentioning
confidence: 99%
“…Various epidemiological studies have drawn a link between the incidence of helminth infection and reduction in allergic and inflammatory diseases (1)(2)(3)(4). In seeking mechanisms by which this might occur, experimental models have linked helminth-induced regulatory T and B cells (Tregs and Bregs, respectively), to the dampening of responses to allergens (5,6) such as HDM (7,8), ovalbumin (OVA) (9,10) and peanut (11), and to the amelioration of inflammation in a number of disease models including colitis (12)(13)(14), experimental autoimmune encephalitis (15), and diabetes (16,17).…”
Section: Introductionmentioning
confidence: 99%